Pengembangan Bisnis Startup Menggunakan Metode SWOT pada Platform Aplikasi Goto Gojek Tokopedia - Nauroh Nazhiifah; Tata Sutabri (Asosiasi Profesi Telekomunikasi dan Informatika Indonesia, 2024)
Startups in Indonesia are growing very quickly which has an impact on the economy in Indonesia. High public enthusiasm is proven by Indonesia being one of the 5 countries with the highest number of startups in the world. There are several startups with good financial valuations that can be said to be unicoms or even decacorns. In this process, capital cannot be separated from the strategies taken by the Company. One alternative funding is to carry out an Initial Public Offering (IPO) on the Indonesia Stock Exchange (BEI). Until 2022, the startup that has carried out an IPO is PT. Goto Gojek Tokopedia conducted a Strength, Weakness, Opportunity, Threats (SWOT) analysis on the two companies to analyze the company's business strategy model. Method used in this research is a descriptive qualitative method and a data collection process by conducting literature studies from accredited scientific publication and digital news sources.